Diagnosis and treatment of iron‑deficiency anaemia in pregnancy and postpartum - C. Breymann; C. Honegger; I. Hоsli; D. Surbek (Publishing House TRILIST, 2023)
Iron deficiency occurs frequently in pregnancy and can be diagnosed by serum ferritin-level measurement (threshold value < 30 μg/L). Screening for iron-deficiency anemia is recommended in every pregnant women, and should be done by serum ferritin-level screening in the first trimester and regular hemoglobin checks at least once per trimester. In the case of iron deficiency with or without anaemia in pregnancy, oral iron therapy should be given as first-line treatment. In the case of severe iron-deficiency anemia, intolerance of oral iron, lack of response to oral iron, or in the case of a clinical need for rapid and efficient treatment of anaemia (e.g., advanced pregnancy), intravenous iron therapy should be administered. In the postpartum period, oral iron therapy should be administered for mild iron-deficiency anemia (haemorrhagic anemia), and intravenous iron therapy for moderately severe-to-severe anemia (Hb < 95 g/L). If there is an indication for intravenous iron therapy in pregnancy or postpartum, ironcontaining drugs which have been studied in well-controlled clinical trials in pregnancy and postpartum such as ferric carboxymaltose must be preferred for safety reasons. While anaphylactic reactions are extremely rare with non-dextrane products, close surveillance during administration is recommended for all intravenous iron products.